Enteric perforation with peritonitis - Meghwal, Sohan Lal; Maida, M. L.; Kharadi, Arjun Lal; Pargi, Mayur Kumar (International Surgery Journal, 2022)
Background: Typhoid fever, also known as enteric fever, is a systemic infection by Salmonella typhi or by the related but less virulent Salmonella paratyphi. Patient with perforation present with sign and symptoms of peritonitis complains of pain abdomen along with distension abdomen, obstipation and vomiting. Enteric perforation in managed surgically. Aims and objective: To study various epidemiological factors in relation with enteric perforation with peritonitis and to compare the outcomes of various procedures of enteric perforation with peritonitis. Methods: The present study was performed on 50 patients of enteric perforation with peritonitis admitted in various surgical wards of RNT medical college hospital, Udaipur. Those patients who underwent conservative treatment or drainage under local anesthesia were not included in this study. Results: Enteric perforation was more common in young males, maximum cases were in 3rd decade followed by 2nd and 4th. Male:female ratio was 1:77:1. Most common symptoms were acute pain abdomen and fever. Constipation (60%) abdominal distension (40%) and vomiting (52%) were other predominate complains. Simple repair of perforation was done in 25 patients. Repair was done in double layer (inner layer) by continuous vicryl and outer by interrupted silk. Mortality was 14%, almost equal irrespective to procedure chosen for management of enteric perforation peritonitis. Conclusions: To deal with enteric perforation(s) operative procedure has to be decided to greater caution taking into consideration patient’s general condition, gut condition, number and site of perforation and contamination of peritoneal cavity.